Proceedings of the 3rd ACM SIGPLAN Workshop on Evaluation and Usability of Programming Languages and Tools 2011
DOI: 10.1145/2089155.2089163
|View full text |Cite
|
Sign up to set email alerts
|

Capturing and analyzing low-level events from the code editor

Abstract: In this paper, we present FLUORITE, a publicly available event logging plugin for Eclipse which captures all of the lowlevel events when using the Eclipse code editor. FLUORITE captures not only what types of events occurred in the code editor, but also more detailed information such as the inserted and deleted text and the specific parameters for each command. This enables the detection of many usage patterns that could otherwise not be recognized, such as "typo correction" that requires knowing that the ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Our own study data also supports this. We found that the backspace keystrokes were 12.41% of all the keystrokes made in the code editor [10]. Note that this is a much higher percentage for backspace compared to normal document editing (e.g., 7.10% in [8]).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our own study data also supports this. We found that the backspace keystrokes were 12.41% of all the keystrokes made in the code editor [10]. Note that this is a much higher percentage for backspace compared to normal document editing (e.g., 7.10% in [8]).…”
Section: Introductionmentioning
confidence: 74%
“…The editing screens and their voice were recorded for further analyses. In addition, we developed and used an event logging plug-in for Eclipse called Fluorite [10] to capture all the low-level editing events. Subjects used the Eclipse IDE version 3.6.2 (Helios) on a laptop running Windows 7.…”
Section: Lab Studymentioning
confidence: 99%
“…Yoon and Myers developed Fluorite [10], an eventlogging plug-in for Eclipse, which captures all of the lowlevel events in the Eclipse code editor. It stores information about each command directly invoked by a user's action (copying or pasting text, moving the cursor position, selecting text by keyboard or mouse, and undoing past commands) and each document change that contains the actual deleted and inserted text.…”
Section: Toolsmentioning
confidence: 99%
“…As a result, it will facilitate programmers' tasks of reusing or modifying existing code in To assist code history exploration, change-based support has recently become available [6], [7]. For example, SpyWare [8], Syde [9], Fluorite [10], CodingTracker [11], and OperationRecorder [12] are embedded into modern integrated development environments (IDEs) and capture all of the fine-grained code changes performed on the editors provided by their respective IDEs. In addition, some of these recording tools collaborate with tools that visualize, filter, and/or replay recorded code changes [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al [52] developed a tool, Fluorite, that records low-level events in Eclipse IDE. Fluorite captures sufficiently precise fine-grained data to reproduce the snapshots of the edited files.…”
Section: Tools For Fine-grained Analysis Of Code Evolutionmentioning
confidence: 99%